PENGARUH HARGA DAN IKLAN TELEVISI TERHADAP KEPUTUSAN PEMBELIAN SHAMPO SUNSILK DI KALANGAN MAHASISWI UNIVERSITAS PALEMBANG - Zubaidah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
The process of making purchasing decisions is a process that starts from the recognition that problems can be solved through the purchase of several products.This study aims to determine the effect of price and television advertising on purchasing decisions among Sunsilk shampoo University student Palembang. The population in this study are all Palembang University student and the sample is in part of the population.The sampling technique is a technique accidental sampling, data analysis using validity, reliability, classic assumption test, multiple regression analysis, t test and F test results showed that the prices are a positive influence and significant price positive and significant effect of 0, 416 Sunsilk shampoo on purchasing decisions among University student Palembang.Television Ads positive and significant effect of 0, 425 on purchasing decisions among Sunsilk shampoo University student Palembang. The variable is the most dominant influence on purchasing decisions is television advertising.